Biological, psychological, and social factors in complicated grief - Wulandari , Ratna; Kusumawati, Mira Wahyu; Albyn, Devanda Faiqh (PT Saintek Medika Nusantara, 2021)
Individuals fail to follow the normative grieving process within a long time and stay in one phase, so it manifests in physiological function and disrupts their life function. This article aims to analyze the role of aspects affecting the problem of complicated grief. A literature review method used is doing a scientific article review obtained from the database. Articles were obtained by browsing online databases, such as Science Direct, EBSCO, and Proquest, with keywords